A crossover comparison of extended release felodipine with prolonged action nifedipine in hypertension. Issue 2 (August 1995) - Moncica, I; Oh, P I; ul Qamar, I; Scolnik, D; Arbus, G S; Hebert, D; Balfe, J W; Koren, G
Abstract : In a crossover design, control of blood pressure by extended release felodipine was compared with control by prolonged action nifedipine in 21 children with renal hypertension. Compliance with once daily felodipine was higher than with nifedipine, at 95.6 (SEM 2.7)% v 78.9 (6.0)% (p = 0.02). Mean diastolic blood pressure was lower during the day with felodipine than with nifedipine, at 77.6 (2.4) v 84.4 (2.8) mm Hg (p = 0.05). Similarly, blood pressure load (the percentage of the day during which the child had blood pressure exceeding the upper limits of normal for age) was lower for felodipine than for nifedipine: 43.5 (5.5)% v 61.3 (6.3)%. There was an opposite trend during the night, though this did not reach statistical significance. These data suggest that once a day felodipine is effective in children with hypertension. This may be because of improved compliance.